2015
DOI: 10.1108/lodj-04-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative supervisor developmental feedback and task-performance

Abstract: Purpose – The purpose of this paper is to conceptualize, understand, and measure positive and negative aspects of supervisor developmental feedback (SDF) and investigate their relationships with task performance. Design/methodology/approach – In Study 1, common themes in SDF were identified and a set of SDF items were developed to capture the positive and negative SDF domain. Study 2 entailed the administration of the items to respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…HR managers and line managers should be aware of the need to assist employees in obtaining ongoing feedback from different sources within the organization because our research has shown that, in the absence of one source of feedback, other sources are critical in enhancing employees’ innovative behavior. Therefore, organizations should not only encourage supervisors to provide feedback as part of the annual formal performance appraisal process (Brown, Kulik, & Lim, ; Zheng, Diaz, Jing, & Chiaburu, ) but also consider implementing an appraisal feedback process for employees through which they can obtain more regular feedback from multiple sources, not only from their direct supervisor but also from other employees in the organization (Biron, Farndale, & Paauwe, ; Kuvaas et al, ). As we have shown, feedback can promote employees’ work engagement and perceptions that the organization is upholding its side of the psychological contract and subsequently foster employees’ innovative behavior (Gruman & Saks, ; Harris, ).…”
Section: Discussionmentioning
confidence: 99%
“…HR managers and line managers should be aware of the need to assist employees in obtaining ongoing feedback from different sources within the organization because our research has shown that, in the absence of one source of feedback, other sources are critical in enhancing employees’ innovative behavior. Therefore, organizations should not only encourage supervisors to provide feedback as part of the annual formal performance appraisal process (Brown, Kulik, & Lim, ; Zheng, Diaz, Jing, & Chiaburu, ) but also consider implementing an appraisal feedback process for employees through which they can obtain more regular feedback from multiple sources, not only from their direct supervisor but also from other employees in the organization (Biron, Farndale, & Paauwe, ; Kuvaas et al, ). As we have shown, feedback can promote employees’ work engagement and perceptions that the organization is upholding its side of the psychological contract and subsequently foster employees’ innovative behavior (Gruman & Saks, ; Harris, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have convincingly demonstrated the positive connection between feedback and performance under various circumstances [2,10,12,13,15]. Favero et al (2016) examined how internal management efforts including performance feedback provision affect school performance.…”
Section: Hypotheses: Performance Feedbacks and Performancementioning
confidence: 99%
“…Scholars [6,8] have suggested that performance feedback may alleviate the negative effects of low goal clarity on performance in public organizations by guiding employees to focus on selected goals that both positive and negative performance feedback effectively helps to enhance performance only if supervisors focus on providing performance information and deliver it consistently [9,15,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Source expertise includes an understanding of the job requirements of the feedback recipient, an understanding of the recipient's actual work requirements, and the ability to accurately determine the performance of the job . Therefore, the supervisor should hold great knowledge of the performance area and know performance criteria so that the source of the information presented is credible and useful (Zheng, Diaz, Jing, & Chiaburu, 2015). The second dimension of the feedback environment is the feedback quality.…”
Section: Literature Review 21 Feedback Environmentmentioning
confidence: 99%